Manajemen Pendidikan di Rumah Qur'an SDIT Bina Insani Muslim Jatimulya Bekasi - Mia Fitriah Elkarimah (Universitas Indraprasta PGRI Jakarta, 2019)
Background this study was the interest of researchers against the management education in the House of the Qur'an Bina Insani Muslims are hereinafter referred to as RQ BIM, which is the flagship program of the ektrakurikuler SD IT BIM. Extracurricular program was developed independently. starting from low grade to grade tingggi with allot time for 4 hours. This research aims to analyze the implementation of management education that includes planning, organizing, implementing, monitoring. Research methods the research was descriptive writers do kualitif. This research was the Chief informant RQ, head of the elementary school IT BIM, and teachers as well as other data that is still closely related to this study. engineering data retrieval is done by way of observation, in-depth interviews, and documentation.. The results of this research it can be concluded that Management RQ BIM already done but rudimentary research results showed: (1) implementation management education RQ BIM is: (a) planning; RQ BIM which has vision and mission, objectives, strategies and development plans activity. (b) organizing the learning through the delivery of the material, learning strategies, and learning methods are used by RQ BIM (c) implementation phases is that cause an organization runs, all of which involved in the organisation should strive towards the aims to conform with the planning. Based on the reality that this is has not been done well (d) supervision, observations indicate that the coordinators of the RQ usually asks and shares to the teachers about the progress of the children, and always establish the teacher’s quality. (2) factors affecting program implementation RQ BIM. (2) Factors affecting program implementation RQ BIM can be divided in two parts; which support RQ programs and inhibit it